Psychoanalytic psychotherapy after child abuse : the treatment of adults and children who have experienced sexual abuse, violence, and neglect in childhood - McQueen, Daniel (Karnac, 2008)
"This book is unique in two ways. Firstly, in bringing together for the first time the considerable scientific evidence of effectiveness and the vast body of accumulated clinical experience using psychoanalytical approaches in the treatment of people who have experienced childhood abuse. Secondly, in being the product of the widest collaboration of individuals and organizations concerned about the effects of child abuse, and experts on child abuse and psychotherapy. These include experts by experience, survivor groups, activists, academics, and clinicians: paediatricians, physicians, child and adult psychiatrists, psychoanalysts, psychologists, and psychoanalytic psychotherapists." "This book is intended for practitioners of psychiatric, psychological, and psychoanalytic therapies and providers of mental health services to children and adults. It should inform Primary Care Trusts, Children's Services commissioners, and health service providers about theoretical approaches and therapeutic practice involved in psychoanalytic psychotherapy after child abuse."--BOOK JACKET.